2019
DOI: 10.1002/lsm.23060
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of six optical coherence tomography systems for vocal fold imaging: A comparison study

Abstract: Objectives There have been many advancements in laryngeal imaging using optical coherence tomography (OCT), with varying system design and probes for use in research, office, and operating room settings. We evaluated the performance of six distinct OCT systems in imaging porcine vocal folds (cords) using computational image processing and segmentation. Methods Porcine vocal folds were scanned using six OCT systems. Imaging system and probe performance were quantitatively assessed for signal penetration, layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Our study also demonstrated the variability in depth penetration of two swept-source OCT systems of varying center wavelengths, namely, 1.3 μm and 1.7 μm. It has been previously indicated that 1.7 μm OCT has a greater penetration depth compared to 1.3 μm, and this was as expected [37][38][39]. Due to the light scattering relationship between the wavelength and particle size, 1.7 μm wavelength light scatters preferentially forward (rather than back or side scattered), permitting light diffusion deeper into the sample.…”
Section: Discussionsupporting
confidence: 55%
“…Our study also demonstrated the variability in depth penetration of two swept-source OCT systems of varying center wavelengths, namely, 1.3 μm and 1.7 μm. It has been previously indicated that 1.7 μm OCT has a greater penetration depth compared to 1.3 μm, and this was as expected [37][38][39]. Due to the light scattering relationship between the wavelength and particle size, 1.7 μm wavelength light scatters preferentially forward (rather than back or side scattered), permitting light diffusion deeper into the sample.…”
Section: Discussionsupporting
confidence: 55%
“…He mentioned in the paper that precise delineation of VF-layered microstructure provides useful information for precise detection of the VF lesions along the unique layered structure [27]. Recent studies [28,29,30] presented the usefulness of this technique especially during surgical intervention to the various types of the VF lesions including VF scars. Heris et al recently characterized the VFs microstructure and elasticity using nonlinear laser scanning microscopy and atomic force microscopy-based indentation, respectively [31].…”
Section: The Unique Microstructure Of the Vf And Imaging The Strucmentioning
confidence: 99%